Blue Economy Analysis in Improving the Lifestyle of Coastal Fisherman With BUMDes/Kampung as Intervening Variables - Hakim, Abdul; Syadiah, Syarifatul (International Conference On Economics Business Management And Accounting (ICOEMA), 2022)
Based on the Blue Economy analysis in improving the standard of living of fishermen on the coast of Berau Regency, it can be concluded that by optimizing marine resources it is very beneficial for the survival of the people on the coast and by using a work system and measuring time and by using the Global Positioning System (GPS) as a tool. fish detectors are very impactful and helpful in the results obtained by fishermen, this can be seen from the increase in fish catches obtained by fishermen. By utilizing technology such as fishing vessels with engine power, work systems and time used as well as the use of the Global Positioning System (GPS) as a fish detection tool, the results obtained are very helpful. A large catch but not supported by an appropriate selling price will harm fishermen so that fishermen remain at the poverty level where the fishermen’s catches are directly sold to the middlemen whose prices are determined by the middlemen so that regardless of the fisherman’s results, it still does not provide the fishermen’s welfare. However, with innovation and government policies towards the establishment of Village/Kampung-Owned Enterprises that play a role in buying fishermen’s catch at a better price, it will benefit fishermen, this can be seen from the results obtained by fishermen before the existence of BUMDes/Kampung and after the existence of BUMDes such as for Traditional Fishermen from income before the existence of BUMDes/Kampung is Rp. 17,747,200 to Rp. 21.507.200, - after the existence of BUMDes/Kampung, and so on for motorcycle fishermen from the results of Rp. 73.160.000,- to Rp. 88.66. 000,- and Modern Fishermen from Rp. 191,264,000,- to Rp. 322,464,000,- This means that the existence of Village/Kampung-Owned Enterprises is very helpful for fishermen in obtaining fish catches and this will spur fishermen to seek or utilize marine resources to the fullest.